Translation shifts in English Indonesian: a cognitive-affective map study - Bessie, Polce Aryanto; Artawa, Ketut; Pastika, I Wayan; Udayana, I Nyoman (Penerbit Universiti Kebangsaan Malaysia, 2024)
Semantic cognition should be considered first when translating. The cognitive process relates to how people determine the component semantics of words in either written or oral text. Simply put, the cognitive process brings semantic labels to one’s mind, which correspond to syntactic labels of a different language discourse. Translators’ efforts to match the meaning of source language (SL) text in the target language (TL) can lead to translation shifts. Therefore, this article focuses on the valence shift between English and Indonesian. The primary source of this article was Start With Why by Sinek (2009) and its Indonesian translation by Purwoko (2019). The analysis applied the Cognitive Affective Map tool. This article explores the translation shift by considering the semantic map by Song (2018) and the blended theory by Ungerer and Schmid (2006). The results of this research indicate that an intrasystem shift occurs. Ergative cases in source language change to nonergative cases, and the entity of semantic argument changes animate cases to be unanimated, or vice versa. In addition, the number of semantic arguments changes. This research implies that translators should define semantic arguments when translating and clarify them with target language speakers' social cognition to find equivalent meanings.